Legal Certainty of Arbitration in The Settlement of Islamic Economic Civil Cases in The Perspective of Positive Law in Indonesia - Saepullah, Usep (Universitas Islam Negeri Raden Intan Lampung, 2022)
One of Law enforcement efforts can be conducted through a non-litigation approach. In this, arbitration can be seen as a non-litigation legal effort and can be used to resolve Islamic economic civil cases. So far, arbitration law effort has been regulated in the Law Number 30 of 1999 and is widely used in the law enforcement practices. This study uses a normative-juridical method and a qualitative approach. The sources and techniques of data collection refers to the number of relevant literatures, and also analyzed deductively and inductively. The results of this study show that legal certainty of arbitration in the settlement of Islamic economic civil cases in the perspective of positive law in Indonesia that regulated in regulated in the Law Number 30 of 1999 has proven to be quite effective in resolving Islamic economic civil cases. The benefit of Islamic economic civil cases settlement through arbitration is the parties have the same position in the form of equality before the law, the process is easy, not expensive, and a win-win solution. Moreover, arbitration can also guarantee legal certainty and justice for the disputing parties.